Inhibition of Mixed Biofilms of Candida albicans and Staphylococcus aureus by β-Caryophyllene-Gold Nanoparticles - Fazlurrahman Khan; Nazia Tabassum; Geum-Jae Jeong; Won-Kyo Jung; Young-Mog Kim (MDPI AG, 2023)
Polymicrobial biofilms, consisting of fungal and bacterial pathogens, often contribute to the failure of antimicrobial treatment. The growing resistance of pathogenic polymicrobial biofilms to antibiotics has led to the development of alternative strategies to combat polymicrobial diseases. To this end, nanoparticles synthesized using natural molecules have received significant attention for disease treatment. Here, gold nanoparticles (AuNPs) were synthesized using β-caryophyllene, a bioactive compound isolated from various plant species. The shape, size, and zeta potential of the synthesized β-c-AuNPs were found to be non-spherical, 17.6 ± 1.2 nm, and -31.76 ± 0.73 mV, respectively. A mixed biofilm of Candida albicans and Staphylococcus aureus was used to test the efficacy of the synthesized β-c-AuNPs. The results revealed a concentration-dependent inhibition of the initial stages of formation of single-species as well as mixed biofilms. Furthermore, β-c-AuNPs also eliminated mature biofilms. Therefore, using β-c-AuNPs to inhibit biofilm and eradicate bacterial-fungal mixed biofilms represents a promising therapeutic approach for controlling polymicrobial infections.